النشأة والتأصيل للتفسير الموضوعي - الموسوي حوراء علي احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
Among the branches of Qur’anic interpretation is thematic exegesis (al-tafsīr al-mawḍūʿī), which is a method of interpretation that gathers various verses related to a single topic and derives beneficial and insightful conclusions. This research examines the origin and development of this type of exegesis, which was practiced by early scholars from the time of the Prophet Muhammad (peace be upon him) and the Imams (peace be upon them) after him. A close study of the efforts of early scholars reveals their clear contributions to this field. Many forms of exegesis were written, some of which have reached us, while others are only known through references in existing scholarly works. It has become evident that this style of interpretation (thematic exegesis) did not fully emerge as a distinct discipline until the 14th century AH, when interest in it became more widespread and systematic. However, the early stages of this method appeared during the Prophet’s time, as indicated in Sahih al-Bukhari (Hadith no. 3428) and Sahih Muslim (Hadith 124), narrated by Abdullah ibn Mas‘ud: When the verse “Those who believe and do not mix their faith with wrongdoing” (Qur’an 6: 82) was revealed, the Companions felt distressed and said, “Who among us has not wronged himself?” The Prophet (peace be upon him) said, “It does not mean that; do you not hear the saying of Luqman to his son, ‘Indeed, associating others with Allah is a great wrongdoing’ (Qur’an 31: 13)? “This clearly indicates that a single word in the Qur’an can have multiple meanings and that understanding the intended meaning requires considering all related verses. Hence, thematic exegesis involves first gaining a comprehensive understanding of the Qur’an through analytical interpretation, then gathering and organizing all verses related to a specific topic, supported by narrations and other sources Some important recommendations include: collecting all verses related to one topic, studying the contextual relationships between surahs, analyzing subjects according to Qur’anic principles, and utilizing linguistic dictionaries for deeper understanding.